Análisis de la vida productiva en razas de bovinos para carne - Ledesma Alvarado, David Rodrigo (2022)
To evaluate the productive life in bovine breeds, all sanitary aspects for cattle are of the utmost importance, such as deworming and the application of vitamins, since this will help the correct reproductive management of both the bull and the female, the management of pregnancy will depend depending on the breed of the cow, it is generally between 280 and 288. An adequate process of fattening the calves must be carried out. Meat production has focused mainly on the use of grasslands as the main food resource for animals, a characteristic that is due to economic reasons, since they are cheap food. The period of productive life corresponds from the first calving to the elimination of the bovine, thus giving a production for life. The productive parameters in cattle are reflected through records, such as puberty, first service, first calving, parturition, environmental factors, nutritional and health factors, averaging the productive life of 42.9 - 29.4 months. It is said that in Ecuador the mestizo breed represents 37.7% and the creole 23.8% of the entire bovine population of the country. The carcass is a component whose content is variable and its quality depends on the relative proportions in terms of bones, muscles and fat, which will depend on the price of the meat. The Aberdeen – Angus breed was determined as one of the most efficient breeds at the level of productive function, recognized for its reproductive precocity, calving ease, maternal aptitude and longevity, males weigh an average of 850 kg and adult females an average of 550kg, thus producing quality meat.